Effects of angiogenic factors and 3D-microenvironments on vascularization within sandwich cultures - Nishiguchi, Akihiro; Matsusaki, Michiya; Asano, Yoshiya; Shimoda, Hiroshi; Akashi, Mitsuru (Biomaterials, 2014)
The in vitro fabrication of vascularized tissue is a key challenge in tissue engineering, but little is known about the mechanisms of blood-capillary formation. Here we investigated the mechanisms of in vitro vascularization using precisely-controlled 3D-microenvironments constructed by a sandwich culture using the cell-accumulation technique. 3D-microenvironments controlled at the single layer level showed that sandwich culture between more than 3 fibroblast-layers induced tubule formation. Moreover, the secretion of angiogenic factors increased upon increasing the number of sandwiching layers, which induced highly dense tubular networks. We found that not only angiogenic factors, but also the 3D-microenvironments of the endothelial cells, especially apical side, played crucial roles in tubule formation in vitro. Based on this knowledge, the introduction of blood and lymph capillaries into mesenchymal stem cell (MSC) tissues was accomplished. These findings would be useful for the in vitro vascularization of various types of engineered organs and studies on angiogenesis.